Lewis and Clark on the Great Plains : a natural history - Johnsgard, Paul A. (University of Nebraska Press, 2003)
Lewis and Clark on the Great Plains is an easy-to-use reference on the wildlife that Meriwether Lewis and William Clark encountered during their 1804-6 Corps of Discovery expedition. More than one hundred animals and plants that were first carefully described and in some cases discovered by Lewis and Clark are identified here. More than accounts of the regional flora and fauna, Lewis and Clark on the Great Plains examines the lasting importance of the expedition's discoveries, the significance of the Plains plants and animals to local Native Americans, and the current status of Plains wildlife. Lavishly illustrated with Paul A. Johnsgard's drawings of mammals, birds, fish, reptiles, and plants, the book also includes a guide to the Lewis and Clark sites of botanical and zoological interest and more than seventy sites where readers can follow in the footsteps of two of America's greatest pioneering naturalists.